Neurological Manifestations In Typhoid Fever During The First Week Of Illness: A Case Report - Shanza Nazish, Tooba Nawaz, Shanza Nazish, Tooba Nawaz (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Typhoid fever, a classical example of enteric fever, is a potentially fatal, multi-systemic illness caused primarily by Salmonella enterica serovar typhi.1 Typhoid is a major public health problem in many developing countries of the world. 80% of the cases of Typhoid are reported from Bangladesh, Pakistan, China, India, Indonesia, Nepal and Vietnam2 . Its classical presentation includes fever, malaise, diffuse abdominal pain, and constipation. However, it can also present with symptoms of confused mental state, acute psychosis, meningo-encephalitis, myelitis, cerebellitis, parkinsonism and generalized anxiety disorders.3,4 Neurological complications following typhoid fever usually occur during the third week of illness. These complications are rarely observed during the first week of illness. Here we report a case of a 17 year old boy who developed sensory aphasia and dystonic jerks during first week of typhoid fever.